Meningkatkan ketuntasan belajar siswa dengan model pembelajaran introduction, connection, aplication, reflection dan extension Kelas VIII dalam tema narrative text pola dakwah Nabi Muhammad SAW. di Madinah mata pelajaran SKI di MTs Negeri Krian Sidoarjo - Nawawi, Syu'aib (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
One of the learning models that includes a series of planned learning experiences arranged in a systematic, operational, and directed way to help students master specific learning objectives is an ICARE learning tool. The objectives of this research are: 1) To compile the learning model of Intellection, connection, aplication, reflection, extension of Class VIII in theme